2018
DOI: 10.1111/ajo.12792
|View full text |Cite
|
Sign up to set email alerts
|

Quality management of nuchal translucency ultrasound measurement in Australia

Abstract: Teleconference tutorials are a convenient, accessible and effective way to obtain immediate and sustained improvement in operator performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 12 publications
1
20
0
2
Order By: Relevance
“…Our prior data were limited in terms of our ability to review provider characteristics, but the current, larger dataset shows that those providers with longer duration within the NTQR program, those with a higher annual volume of scans, and those with more NT-credentialed providers at their practice site had greater accuracy of measurement (higher NT median MoM) and greater consistency of measurement (lower SD of log 10 NT MoM). This is similar to findings of other studies, in which providers with low annual scan volumes and less experienced providers were more likely to be assigned remediation or require additional monitoring 19,25 . However, other studies have not shown a clear relationship of individual providers' consistency of measurement with their annual scan volume, finding an association only with operator experience 26,27 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our prior data were limited in terms of our ability to review provider characteristics, but the current, larger dataset shows that those providers with longer duration within the NTQR program, those with a higher annual volume of scans, and those with more NT-credentialed providers at their practice site had greater accuracy of measurement (higher NT median MoM) and greater consistency of measurement (lower SD of log 10 NT MoM). This is similar to findings of other studies, in which providers with low annual scan volumes and less experienced providers were more likely to be assigned remediation or require additional monitoring 19,25 . However, other studies have not shown a clear relationship of individual providers' consistency of measurement with their annual scan volume, finding an association only with operator experience 26,27 .…”
Section: Discussionsupporting
confidence: 89%
“…The NTQR data have been able to provide a robust, detailed NT referent curve for the majority of the USA population that underwent NT screening over the 15-year period from January 2005 to December 2019, and these data confirm that ongoing assessment of accuracy through a national registry and feedback program has resulted in significant improvement and consistency within this single measured analyte for first-trimester screening, with more than 85% of physicians and sonologists providing consistent measurements within appropriate ranges 9,11,19,24 . Our prior data were limited in terms of our ability to review provider characteristics, but the current, larger dataset shows that those providers with longer duration within the NTQR program, those with a higher annual volume of scans, and those with more NT-credentialed providers at their practice site had greater accuracy of measurement (higher NT median MoM) and greater consistency of measurement (lower SD of log 10 NT MoM).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Nisbet et al proposed 1‐hour teleconference tutorials led by senior sonographers as a method to improve NT measurement quality. Improvement in NT measurement was seen after one audit cycle and was maintained over subsequent years, but they did not find statistically differences with the cohort group . In addition, sonologists with significant deviations could require retraining and exhaustive ultrasound supervision by expert sonologists .…”
Section: Discussionmentioning
confidence: 90%
“…Improvement in NT measurement was seen after one audit cycle and was maintained over subsequent years, but they did not find statistically differences with the cohort group. 27 In addition, sonologists with significant deviations could require retraining and exhaustive ultrasound supervision by expert sonologists. 8,26 This approach could be useful to reduce deviation and improve quality.…”
Section: Discussionmentioning
confidence: 99%